Anti-fertility Effect of Stem bark of Ailanthus excelsa in Wistar Albino Rats - Mani, Munesh; Rathore, Devendra S (Current Research in Pharmaceutical Sciences, 2016)
Ailanthus excelsa (Family: Simaroubaceae) is commonly known as Mahanimba and Arlu. In this study stem bark of Ailanthus excelsa were evaluated by anti-implantation and abortifacient method at three doses i.e. 100mg/Kg, 150mg/Kg and 200mg/Kg of the body weight of the rat. It was observed that treatment with methanolic extract of Ailanthus excelsa at the dose of 200 mg/kg was shown significant anti-fertility effect. Ailanthus excelsa possess anti-fertility activity by inhibiting implantation and abortifacient action.